La récupération de l’eau de pluie dans les bâtiments : les enjeux d’une pratique de décentralisation partielle de la gestion des services d’eau - Bernard De Gouvello (Cybergeo, 2004)
With the intention of a more rational water resources management, an idea is growing in France: rainwater harvesting and reuse for uses which are not requiring drinking water quality. Firstly developed in individual houses, such practices now appear in collective buildings projects. Nevertheless, putting into practice, this idea faces several difficulties: regulation, economic, technical, organizational, even cultural ones.